Development of Attacking Strategies in Badminton Double Category: Construct Validity and Inter-Rater Reliability - Zidane Aryasatya Adyan; Suratman; Hadi; Dewangga Yudhistira (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
One of the game categories in badminton is doubles. Doubles games demand consistency in launching attacks that require physical aspects and complex strategies. The purpose of this study is to validate and develop the concept of attack strategy in badminton games in the doubles category. The research method is 3D. Participants were documents in the form of articles and 6 material experts, 3 national licensed coaches, and 3 academics with master's and doctoral degrees specializing in badminton. The data analysis technique used Aiken's content validity. The research stages include (1) Define, defining and analyzing the needs to develop attacking strategy products, (2) Design, analyzing articles and videos and designing a 1-5 Likert scale questionnaire to refine the development of attacking strategy products, (3) Development, assessing attacking strategy products with Delphi techniques until consensus from 6 experts. Inter-Rater Reliability Test using Cronbach's Alpha and Inter-Rater Agreement Test using ICC. Based on the results of the study, it was found that the content validity value and Cronbach's Alpha value were 0.265>0.6 and 0.71-1.00, respectively. In addition, the ICC value of a single measurement was 0.30 with a mean measurement value of 0.157>0.75. In conclusion, the construct of attacking strategy in badminton doubles has a high and good level of content validity. The concept of attacking strategy can be a recommendation for badminton coaches to apply the concept that the author developed.